A Economic and Financial Feasibility Analysis of Infrastructure Development Projects in Underdeveloped Areas in Aouthheast Aceh - Harahap, Kartiyani (Quantitative Economics Journal, 2025)
Infrastructure development in underdeveloped areas is one of the main priorities in efforts to equalize development in Indonesia. Southeast Aceh Regency, as a region with geographical and economic challenges, requires infrastructure development that can improve connectivity and community welfare. This study aims to analyze the economic and financial feasibility of road and bridge construction projects in Southeast Aceh Regency. The methods used in this study are cost-benefit analysis (CBA), Net Present Value (NPV), Internal Rate of Return (IRR), and Benefit-Cost Ratio (BCR). The results of the study indicate that this project is financially feasible with a positive NPV of IDR 6,500,000,000, an IRR of 8%, and a BCR of 1.1. Economically, this project provides significant social benefits, although the financial returns are relatively low. Increased access to markets, health facilities, and education are expected to improve the quality of life of the community. Although this project does not provide very high financial returns, the social benefits obtained are much greater, so this project is feasible to implement with support from the government and community participation.